1999
DOI: 10.1063/1.125039
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of minority carriers diffusion length using Kelvin probe force microscopy

Abstract: We report on the use of Kelvin force microscopy as a method for measuring very short minority carrier diffusion length in semiconductors. The method is based on measuring the surface photovoltage between the tip of an atomic force microscope and the surface of an illuminated semiconductor junction. The photogenerated carriers diffuse to the junction, and change the contact potential difference between the tip and the sample as a function of the distance from the junction edge. The diffusion length L is then ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…[51] Another very interesting application of KPFM has been the measurement of minority-carrier diffusion length in conventional semiconductors. [52,53] The method is based on the study of the surface photoinduced voltage between the SFM tip and the surface of an illuminated semiconductor p-n junction. The photogenerated carriers diffuse to the junction and change the voltage difference between the tip and the sample as a function of the horizontal distance from the p-n junction.…”
Section: Kpfm Of Conventional Inorganic Materialsmentioning
confidence: 99%
“…[51] Another very interesting application of KPFM has been the measurement of minority-carrier diffusion length in conventional semiconductors. [52,53] The method is based on the study of the surface photoinduced voltage between the SFM tip and the surface of an illuminated semiconductor p-n junction. The photogenerated carriers diffuse to the junction and change the voltage difference between the tip and the sample as a function of the horizontal distance from the p-n junction.…”
Section: Kpfm Of Conventional Inorganic Materialsmentioning
confidence: 99%
“…Despite these challenges, the need to examine variations in local potential in electronic nanodevices spurred efforts to overcome some of the obstacles with careful analytical treatments that determined limits in quantification and allowed complex materials to be addressed. The late 1990s saw SSPM applied to semiconductor, 43,44 organic, 45 and ferroelectric 46,47 surfaces, as well as to defects, 48,49 and photoinduced 50,51 and thermal phenomena 52 in these materials. It is fair to say at this point that absolute values of potential cannot be quantified, but variations in potential can be determined with energy resolution of 2–4 meV and spatial resolution of the order of 50–100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…SPM has been successfully applied to semiconductor, 19 organic, 20 and ferroelectric 21,22 surfaces, as well as to defects, 23,24 and photoinduced 25,26 and thermal phenomena 27,28 in these materials. A number of SPM studies on grain boundary related phenomena have also been reported.…”
Section: Introductionmentioning
confidence: 99%